Agronomic Requirements for Organic Cultivation of Andrographis Paniculata (Burm) Nees. In the Upper Brahmaputra Valley Agroclimatic Zone of India - Upadhyaya, S.; Saikia, L. R. (Indian Forester, 2015)
Effect of planting material and time, spacing and organic manures on biomass production of Andrographis paniculata was studied at Dibrugarh University under upper Brahmaputra valley agroclimatic zone (UBVAZ) of India during 2006-2011. It revealed that April to September is found to be the best period and direct seeded technique is seems to be the best for A. paniculata cultivation under UBVAZ. Maximum biomass (4.20 t ha-1 dry wt.) was obtained in cowdung @ 12 t ha-1 with maximum economic benefit (profit 51, 870/-ha-1). Further, it showed that 30 cm Ã— 30 cm plant to plant and row to row spacing recorded maximum yield in all the cases of manure treatment.